Motif Penggunaan Fake Account Pada Media Instagram di Kalangan Mahasiswa Universitas Ddharma Andalas - Fitria, Sonia Aljeria; Eriend, Dion (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This study aims to understand the main motives driving students at Dharma Andalas University to use fake accounts on their Instagram social media. This research is conducted due to the prevalent phenomenon where an Instagram user has more than one account with various reasons supporting their possession of these accounts. On these secondary accounts, users often use pseudonyms, false addresses, and significantly different information, which can be categorized as fake accounts. The theory used in this research is Alfred Schutz's Phenomenology theory, which explains how to understand the social actions of an individual or a group. The research method used is qualitative with a phenomenological approach. This method aims to capture the meaning of human life experiences about a phenomenon to further understand the structure of consciousness in human social experiences. Informant selection for the study used purposive sampling techniques as conveyed by Creswell (2018), requiring 3-10 research subjects with certain criteria. The results of this study identified various causes and purposes that become the main motives for students to have fake accounts on Instagram, whether due to the environment or experiences while using Instagram, or for the purpose of easier self-expression or supporting activities. With all the challenges of using Instagram, which has a vast network, it is hoped that users can remain wise when using Instagram or other social media to protect their privacy and that of others.